Targeted proteomics strategy applied to biomarker evaluation. Issue 11 (31st October 2013) - Kim, Yeoun Jin; Gallien, Sebastien; van, Jan; Domon, Bruno; Sauer, Sascha
<x xml:space="preserve">Abstract</x> The evaluation of biomarker candidates, involving quantitative measurement of a large number of proteins in bodily fluids, remains the main obstruction in the development of a biomarker validation pipeline. Although immunoassays are commonly used, high‐throughput and multiplex‐capable methods are required for expediting the evaluation process. MS‐based approaches employing targeted proteomic strategies provide not only a sensitive, but in addition a precise quantification tool, which is versatile, systematic, and scalable. Its capability of multiplexing hundreds of targets facilitate a cost‐effective and rapid evaluation and is especially useful during the early stage of the process where a large list of candidate biomarkers must be triaged before entering validation studies. The robustness requirement for the methods also mandates a high degree of selectivity to analyze complex clinical samples. Improvement in the selectivity of LC‐MS methods has been achieved by adopting high‐resolution and high‐accuracy mass analyzers to perform quantitative analyses with a novel method called parallel reaction monitoring. This article discusses the design and performance of biomarker evaluation studies using targeted proteomics strategies and the implementation of recent technology developments.